The Urgency of English Language in Tourist Destinations: Enhancing the Comfort and Safety of Foreign Tourists in the Tanjung Bira Beach Area, Bulukumba Regency, South Sulawesi - Fathayadimyati, Irfan Hakim; Al-Farizi, Reza; Mulyaningsih, Mulyaningsih; Wasiyah, Wasiyah; Rohiyati, Rohiyati (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
English plays a crucial role in the tourism sector, especially in local tourist destinations such as Tanjung Bira Beach. The ability to communicate in English by tourism stakeholders is key to enhancing the comfort and safety of foreign tourists. This article discusses the urgency of English language proficiency in tourist areas, considering the important role of language in conveying information, explaining local culture, and responding to emergency situations. Additionally, English is a vital element in creating positive experiences for foreign tourists, increasing the competitiveness of destinations, and supporting sustainable tourism growth. Through structured English language training, the provision of multilingual informational materials, and the utilization of digital technology, it is hoped that tourism stakeholders in Tanjung Bira Beach can enhance their service quality. With this approach, tourist destinations will not only become more welcoming to foreign tourists but also provide positive contributions to the local economy. This article emphasizes the need for synergy between local governments, tourism stakeholders, and the community to ensure that English language proficiency becomes an integral part of sustainable tourism development.